Stakeholders interest and influence and their interactions in managing natural resources in Lake Hawassa Catchment, Ethiopia - Mekuria, Wolde; Haileslassie, Amare; Tengberg, A.; Zazu, C. (Informa UK Limited, 2021)
This study was conducted in Lake Hawassa catchment, Ethiopia where policy programs are aiming to restore degraded lands with participation of local stakeholders. We assessed the system in relation to natural resource management and degradation using the Intergovernmental Platform on Biodiversity and Ecosystem Services (IPBES) conceptual framework and conducted a stakeholder analysis to understand stakeholder interest, influence and interactions amongst the different categories of stakeholders. Data were collected using key informant interviews, field observation and a literature review. Results indicate that the degradation of natural resources in the catchment is attributed to several interlinked socio-economic and biophysical factors. Identified stakeholders include government and non-governmental organizations, local administrative bodies, civil society, the private sector and farmers. Most of the stakeholders have a role in landscape restoration, have similar interests and strategic options, and are flexible and innovative. Moderate to pronounced trust exists among identified stakeholders and could provide an opportunity to achieve better coordination and collective action amongst the different stakeholders. However, considerable differences between stakeholders in power, power resources and influence were detected due to differences in access to information, communication and negotiation skills, practical relevance, and social relations. The costs for empowerment measures could be low, as many of the stakeholders have access to and control of resources and high level of basic competencies. Our findings could guide practitioners and policy makers on whom and how to engage when planning and implementing natural resources management and landscape restoration interventions at catchment level.